An Unusual Presentation of Rhinophyma as Heminose Hypertrophy - P Kumar; M Ohri (Indian Journal of Plastic Surgery)
An unusual case of rhinophyma in a 20-year-old male presenting as hemi-nose hypertrophy is reported. The histopathological features were suggestive of acne rosacea turning to rhinophyma.